201 Transnasal Endoscopic Approach for Pediatric Skull Base Tumors: A Case Series. (August 2016) - Quon, Jennifer L.; Hwang, Peter H.; Edwards, Michael S.B.
Abstract : INTRODUCTION: Transnasal endoscopic transphenoidal approaches are an essential technique for the resection of skull base tumors in adults. Originally devised and most commonly used to treat pituitary adenomas, they have also been used for a variety of other pathologies. However, in the pediatric population, sellar and suprasellar lesions have historically involved a craniotomy. Transnasal endoscopic transphenoidal techniques in children have only been reported as single case reports and only in regard to purely sellar lesions. METHODS: We present the first reported series of transnasal endoscopic transphenoidal approaches for pediatric skull base tumors. We performed a retrospective review of pediatric patients at our institution who had undergone endoscopic transphenoidal approaches for either a biopsy or resection of their sellar or suprasellar lesions between 2000 and 2015. RESULTS: Our series included 29 patients with ages ranging between 4 and 17 years. Headache (59%), visual changes (55%), and diabetes insipidus (34%) were the predominant presenting symptoms. Twenty-six patients (90%) noted some improvement in their symptoms postoperatively. The majority of patients had secreting pituitary adenomas (38%) followed by Rathke cleft cysts/craniopharyngiomas (31%) and germinomas (13%). Other pathologies included lymphocytic hypophysitis, mature teratoma, and clival chordoma. Patients primarily underwent gross total resections (56%) with a low rate (27.5%) of reresection. Only 2 cases (7%) necessitated a subsequent craniotomy for tumor regrowth into anatomically challenging areas. Eleven (30%) patients had septal flaps, 17 (46%) had fat grafts, and 13 (45%) had intraoperative placement of a lumbar drain. Two patients (7%) had postoperative cerebrospinal fluid leak. The majority of patients (79%) required hormonal supplementation following resection, with fewer requiring subsequent chemotherapy (24%) and radiation (24%). CONCLUSION: Transnasal endoscopic transphenoidal approaches are preferable to craniotomy and are safe and effective for accessing sellar, suprasellar and parasellar lesions in children. Further refinement in technology will allow for more widespread use in the pediatric population.